Association between speed, repeated sprint ability and aerobic endurance parameters in professional Greek soccer players - Volianitis, S.; Bakas, G.; Flouris, A. D.; Famisis, K. (Inquiries in Sport & Physical Education, 2019)
We examined the association between speed, repeated sprint ability (RSA), and aerobic endurance parameters. At the beginning of the preparation period, 18 professional soccer players performed a speed test to determine first step quickness (5 m), acceleration (10 m) and maximal speed (30 m) performance, an RSA test consisting of 6 x 40 m with 20s active recovery, and an incremental treadmill test to determine endurance parameters (velocity at 2mM (V2), 4mM (V4) lactate and maximal velocity (Vpeak)). Best time in a single trial (RSAbest) was moderately correlated to Vpeak (r=-0.36; 90%CL, -0.66 to 0.05) and 30 m (r=0.32; 90%CL, -0.09 to 0.34). Mean RSA was almost perfectly correlated to RSAbest (r=0.93; 90%CL, 0.84 to 0.94), and moderately correlated to V4 (r=-0.46; 90%CL, -0.73 to 0.07) and Vpeak (r=-0.42; 90%CL, -0.70 to 0.02). Percent speed decrement (%dec) was moderately correlated to V2 (r=-0.36; 90%CL, -0.66 to 0.05) and to V4 (r=-0.32; 90%CL, -0.64 to 0.09) expressed as % of Vpeak. These findings indicate that, at the start of the preparation period, RSA is more related to aerobic endurance than speed parameters in professional Greek soccer players.